The Legal Transformation of Zakat and Wakaf in Indonesia: A Bibliometric Analysis and Literature Review for the 2020–2025 Period - Grazia Fontana Bungkundapu; Ahmad Levi Fachrul Avivy (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2026)
This study aims to analyze the development of research on the legal transformation of zakat and waqf in Indonesia through a Systematic Literature Review (SLR) combined with bibliometric analysis. The legal transformation of zakat and waqf refers to the shift from personal religious obligations into nationally regulated legal and economic instruments governed by formal institutions. The research used a mixed method approach by combining bibliometric analysis using VOSviewer software and a systematic literature review of articles indexed in the Scopus database for 60 articles indexed in Scopus during the 2020–2025 period. The findings indicate a significant increase in publications related to zakat and waqf during the observed period. Network visualization identifies four dominant themes: institutionalization of zakat and waqf, governance and accountability, Islamic social finance, and digitalization and financial technology. Overlay visualization reveals a shift in research focus from normative discussions toward institutional governance, digital waqf innovation, and the effectiveness of Islamic social finance institutions. The study concludes that the legal transformation of zakat and waqf in Indonesia reflects not only the formal incorporation of Islamic norms into the national legal system but also the integration of Islamic law, modern governance, and maqasid al-shariah-oriented economic development. This research contributes to the Islamic economic law literature by providing an integrative perspective on the relationship between regulation, institutional development, and socio-economic transformation in zakat and waqf management.